The Nietzsche on plastic forceé: From Musical Harmony to Overhuman - Guibert Elizalde, María (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
The few works that consider the plastic force (plastische Kraft) in Nietzsche focus especially on the definition of the Second Untimely Meditation (1874). The objective of this article is twofold: to demonstrate A) that, beyond the Second Untimely Meditation, this concept has a long history in Nietzsche’s thought that has not been discovered yet and that, as a reflection of the latter, B) the concept of plastic force undergoes an evolution, through which it passes from being the appropriation of an aesthetic concept from the 18th and 19th centuries, to be a characteristic of the free spirit and, therefore, of the overhuman.